Interspecies interactions are an integral determinant of microbial community dynamics - Aziz, Fatma A. A.; Suzuki, Kenshi; Ohtaki, Akihiro; Sagegami, Keita; Hirai, Hidetaka; Seno, Jun; Mizuno, Naoko; Inuzuka, Yuma; Saito, Yasuhisa; Tashiro, Yosuke; Hiraishi, Akira; Futamata, Hiroyuki (Frontiers in Microbiology, 2015)
This study investigated the factor that the determine the dynamics of bacterial communities in a complex system using multidisciplinary methods. Since real and engineered microbial ecosystems are too complex, six types of synthetic microbial ecosystems (SMEs) were constructed under chemostat conditions with phenol as the sole carbon and energy source. 2-4 phenol-degrading, phylogenetically and physiologically different bacterial strains were used in each SEM. Phylogeny was based on the nucleotide sequence of 16S rRNA genes, while physiologic traits were based on kinetic and growth parameters on phenol. Two metrics, J parameter and ‘complex interaction’, were compared to predict which strain would become dominant in a SME. The J parameter is calculated from kinetic and growth parameters, whereas ‘complex interaction’, which was developed here, evaluated bacterial community dynamics by measuring specific growth activity as affected by the other strains. The specific growth activity was calculated as the proportion of growth activity under the presence of supernatant compared to control conditions. Population densities of strains used in SMEs were enumerated by real-time PCR targeting the gene encoding the large subunit of phenol hydroxylase and were compared to predictions made from J parameter and complex interaction calculations. In 4 of 6 SEMs tested the final dominant strain shown by real-time PCR analyses coincided with the strain predicted by both the J parameter and the complex interaction. However, in SMEII-2 and SMEII-3 the final dominant Variovorax strains coincided with prediction of the complex interaction but not the J parameter. These results demonstrate that the effects of complex interactions within microbial communities contribute to determining the dynamics of the microbial ecosystem.